Mecanismos de toxicidade do fipronil em hepatócitos isolados de rato - Guelfi, Marieli [UNESP] (2015)
Fipronil is an insecticide of broad-spectrum action used extensively for pest control. There are reports in the literature of animals and humans poisoning caused by the compound, ocacioning. Thus, it becomes quite important to elucidate the mechanisms of hepatotoxicity of the insecticide for treatment in case of intoxication by mammals. The aim of this study was to characterize the mechanism of toxicity of fipronil in isolated rat hepatocytes and the effect of biotransformation on its toxicological potential. The toxicity of fipronil was assessed by monitoring oxygen consumption and mitochondrial membrane potential, intracellular ATP concentration, Ca 2+ homeostasis and cell viability. The cell viability was evaluated by the tripan blue exclusion in hepatocytes isolated from normal rats and the activity of the enzyme alanine transaminase (ALT) and aspartate transaminase (AST) in hepatocytes isolated from normal rats or rats pretreated with proadifen, a cytochrome P450 inhibitor. Fipronil reduced mitochondrial respiration in cells energized with glutamate plus malate in a dose- dependent manner, and dissipated the mitochondrial membrane potential accompanied by reductions in ATP concentration and a disruption of intracellular Ca 2+ homeostasis. Cell viability was affected by fipronil with higher potency in hepatocytes isolated from normal rats, indicating that the metabolism of insecticide increases its toxicological potential. The results of this study indicate that the toxicity of fipronil to the hepatocytes is related to the inhibition of mitochondrial activity, leading to a decreased ATP synthesis and consequent alteration in intracellular Ca 2+ homeostasis, resulting in cell death